Pet therapy: an effective strategy to care for the elderly? An experimental study in a nursing home - Sollami, Alfonso; Gianferrari, Elisa; Alfieri, Manuela; Artioli, Giovanna; Taffurelli, Chiara (Acta Biomedica Atenei Parmensis, 2017)
Background and Aim: There has recently been a growing interest towards patients’ affective and emotional needs, especially in relational therapies, which are considered vital as to increase the understanding of those needs and patients’ well-being. In particular, we paid attention to those patients who are forced to spend the last phase of their existence in residential facilities, namely elderly people in nursing homes, who often feel marginalized, useless, depressed, unstimulated or unable to communicate. The aim of this study is to verify the effectiveness of pet therapy in improving well-being in the elderly living in a nursing home. Methods: This is a longitudinal study with before and after intervention variables measurement in two groups of patients of a nursing home for elderly people. One group followed an AAI intervention (experimental group) the other one did not (control group). As to perform an assessment of well-being we measured the following dimensions in patients: anxiety (HAM-A), depression (GDS), apathy (AES), loneliness (UCLA), and quality of life (QUALID). Both groups filled the questionnaires as to measure the target variables (time 0). Once finished the scheduled meetings (time 1), all the participants, including the control group, filled the same questionnaires. Results: In accordance with scientific evidence the results confirmed a significant reduction of the measured variables. Especially for the quality of life, which showed a greater reduction than the other. Conclusions: The implementation and success of the Pet Therapy could have a great emotional and social impact, bringing relief to patients and their family members, but also to health professionals.